Customization of surface wettability of nano-SiO2 by coating Trimethoxy(vinyl)silane modifier for oil-water separation: Fabrication of metal-based functional superwetting nanomaterial, characterizations and performance evaluation. (December 2022) - Baig, Umair; Faizan, M.; Dastageer, M.A.; Gondal, M.A.
Abstract: The wettability of nano-SiO2 surface was transformed from the inherent hydrophilicity to functional superhyderophobicity by coating Trimethoxy (vinyl)silane modifier, and the resultant surface showed contrasting wettability for water and oil (Superhydrophobic and Superoleophilic), which is a desired characteristic for the membranes used in oil-water separation. Initially Trimethoxy (vinyl)silane coated SiO2 nanoparticles (TMVS@SiO2 ) were synthesized by hydrolysis and poly-condensation reactions, and this nano dispersion was spray coated on the annealed stainless-steel mesh surface, whose resulting hierarchical surface texture brought about the desired wettability, with the water-surface-air (θWA ) and oil-surface-air (θOA ) interfacial contact angles of 150° and 0° respectively. In addition to the wettability studies (contact angles), FTIR, morphological, and elemental characterizations of the TMVS@SiO2 coated surfaces were carried out to understand the alterations that have taken place on the TMVS@SiO2 surface that in turn rendered superhydrophobicity and superoleophilicity to the surface. The FTIR absorption peaks indicate that after modifying SiO2 with TMVS, the –OH groups on SiO2 surface are clearly replaced by –CH3 . The morphological studies indicated that modification of SiO2 leads to better cross-linking between coating composition and nanoparticles and EDS spectra and elemental mapping of the modified surface showed the presence of Si, O and C elements. Finally, this surface was tested for its efficiency and stability as a membrane in the process of separating oil and water from the oily water using gravity driven method. The oil-water separation efficiency was estimated to be 99% for this membrane and also it was found to be quite stable as the surface effectively retained this oil-water separation efficiency even after 10 cycles of separation process. Graphical abstract: Image 1 Highlights: Fabrication of metal-based functional super-wetting nanomaterial. Fabricated functional nanomaterial is superhydrophobic and superoleophilic. Customization of surface-wettability of SiO2 by coating TMVS for oil-water separation. Membrane fabricated by spray-coating of TMVS@SiO2 NPs on the SS mesh. Oil water separation efficiency was estimated to be 99% for this membrane.